NFTs and Porto Ferreira's premium : a blue ocean or an ephemeral bet on differentiation? - Coelho, Mariana Andrade da Silva Cardoso (2022)
Although Portugal plays an important role in the commercialization of Port Wine, the consumption of this wine has decreased in recent years. In this Master's Final Work (TFM) is presented a strategy to reverse the downward trend of its consumption, more specifically in Porto Ferreira's Premium. Sogrape is a company with an important weight in the national Port Wine market, which makes it a pertinent case study. Thus, we propose to answer the following Research Question: "How to reverse the decreasing trend in Porto Ferreira's Premium Port Wine consumption through NFTs?”. The objective is to understand which factors impact the performance of the Port Wine industry to create a strategy that meets the market needs. To this end, the method used in this work is qualitative, adopting an exploratory case study. In order to reverse this downward trajectory, the creation of a Blue Ocean strategy is proposed. Therefore, and to create a new market and new demand, it is then proposed that Sogrape and its Porto Ferreira Premiums enter the world of digital property, through NFTs. It was concluded, given the opportunities and risks that can be faced when operating in this market, that the integration of Sogrape and its Porto Ferreira Premiums in NFTs is viable.